Soft Skills Analysis of Educational Student in Vocational Study Program of Mechanical Engineering Ivet University - Ariwibowo, Bayu; Sudana, I Made; Atika, Atika; Makruf, Agus (Journal of Vocational and Career Education, 2020)
Soft skills are very needed for every educator. Soft skills encourage the technical skill in self or even institutional development. This research was aimed to analyze 11 kinds of soft skills that is important for prospective educators to have. This research was done in form of descriptive analysis by using quantitative approach. The sample of this research was the students of IVET University as prospective educators for Vocational School in Technological Engineering field. The number of the sample was 80 students. The result showed that almost all respondents have good soft skills; the score was 6859 by 9600 total score. It’s same with 71,4%. The highest score was reached from indicator of enthusiasm at work, that was 86,4%. The lowest score was got by the capability of prospective educators from indicator of creative and innovative thinking, that was 51,9%. Based on this research, educational method or training in increasing the students’ soft skills for prospective educators have to be done, especially in indicator of critical, creative, and innovative thinking.